Seeking optimal confusion: a review on epistemic emotion management in interactive digital learning environments. Issue 2 (17th February 2019) - Arguel, Amaël; Lockyer, Lori; Kennedy, Gregor; Lodge, Jason M.; Pachman, Mariya
ABSTRACT: Emotions play a significant part in students' learning experiences within complex educational environments. However, the impact of emotional experiences on effective learning is not straightforward. For example, being confused during learning may be perceived as an adverse event. There is, however, considerable research evidence suggesting that confusion can also be a productive aspect of a student's learning processes. Despite this, research also suggests that when confusion is persistent it can become harmful, promoting learner frustration or boredom. Key challenges for the design of interactive digital learning environments (IDLEs) are to detect and assess students' emotions and to tailor the environment accordingly. In this paper we examine, from a review of the literature, the implications of learners' confusion that can occur in IDLEs. Strategies for managing students' confusion will then be discussed and examples of features enhancing learning in IDLEs will be suggested.